Tryptophan Scanning Mutagenesis Identifies the Molecular Determinants of Distinct Barttin Functions - Wojciechowski, Daniel (J Biol Chem, 2015)
CLC-K chloride channels are expressed in the kidney and in the inner ear and require the accessory subunit barttin for proper function and membrane insertion. Barttin exerts multiple functions on CLC-proteins: it modifies protein stability and intracellular trafficking as well as channel activity, ion conduction, and gating. So far, the molecular determinants of these distinct barttin functions have remained elusive. Here we performed serial perturbation mutagenesis to identify the sequence determinants of barttin function. Barttin consists of two transmembrane helices followed by a long intracellular carboxyl terminus, and earlier work demonstrated that the transmembrane core of barttin suffices for most effects on the α-subunit. We individually substituted every amino acid of the predicted transmembrane core (amino acids 9–26 and 35–55) with tryptophan, co-expressed mutant barttin with hClC-Ka or V166E rClC-K1, and characterized CLC-K/barttin channels by patch clamp techniques, biochemistry, and confocal microscopy. The majority of mutations left the chaperone function of barttin, i.e. the effects on endoplasmic reticulum exit and surface membrane insertion, unaffected. In contrast, tryptophan insertion at multiple positions resulted in impaired activity of hClC-Ka/barttin and changes in gating of V166E rClC-K1/barttin. These results demonstrate that mutations in a cluster of hydrophobic residues within transmembrane domain 1 affect barttin-CLC-K interaction and impair gating modification by the accessory subunit. Whereas tight interaction is necessary for functional modification, even impaired association of barttin and CLC-K suffices for normal intracellular trafficking. Our findings allow definition of a likely interaction surface and clarify the mechanisms underlying CLC-K channel modification by barttin.